This is not a leadership book : 20 rules for success - Gobillot, Emmanuel (Routledge, 2024)
"Part leadership book, part business book and 100% true, reading this is like hearing a wise, honest and humorous mentor finally tell you about the world of business as it is and how to find your place in it. Many leadership books are either shallow-focusing on only one element of leadership, narrow-examining leadership out of context, or biased-selling an idealized model. This book seeks simplicity without being simplistic and focuses on the reader in their context rather than describing other people's leadership in theirs, setting out 20 rules for success that draw on Emmanuel Gobillot's 20 years of experience advising high performing leaders. Each rule is presented in an engaging and instantly recognisable true story that helps current and aspiring leaders to look differently at their own situation. Best described as a leadership development programme in a book, open this and begin your fast-paced journey from what it takes to be a leader, to why you can be one, via how to succeed"-- Provided by publisher.
Keywords: Leadership.; Leadership -- Case studies.; Organizational change.; Success in business.; elektronické knihy; electronic books